Answer :

Given, and x2 = –1.

We need to prove (A + B)2 = A2 + B2.

Let us evaluate the LHS and the RHS one at a time.

To find the LHS, we will first calculate A + B.

We know (A + B)2 = (A + B)(A + B).

( x2 = –1)

To find the RHS, we will first calculate A2 and B2.

We know A2 = A × A.

( x2 = –1)

Similarly, we also have B2 = B × B.

Now, the RHS is A2 + B2.

Thus, (A + B)2 = A2 + B2.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

Using matrices, sMathematics - Board Papers

If possible, usinMathematics - Exemplar

If possible, usinMathematics - Exemplar

Using matrices, sMathematics - Board Papers

Prove that <span Mathematics - Board Papers

Find the value ofMathematics - Board Papers

If A is a <span lMathematics - Board Papers